A Systematic Review of the Reporting of Adverse Events Associated with Medical Herb use among Children. Issue 2 (March 2013) - Gardiner, Paula; Adams, Denise; Filippelli, Amanda C.; Nasser, Hafsa; Saper, Robert; White, Laura; Vohra, Sunita
Purpose: Information about the safety of herbal medicine often comes from case reports published in the medical literature, thus necessitating good quality reporting of these adverse events. The purpose of this study was to perform a systematic review of the comprehensiveness of reporting of published case reports of adverse events associated with herb use in the pediatric population. Methods: Electronic literature search included 7 databases and a manual search of retrieved articles from inception through 2010. We included published case reports and case series that reported an adverse event associated with exposure to an herbal product by children under the age of 18 years old. We used descriptive statistics. Based on the International Society of Epidemiology's "Guidelines for Submitting Adverse Events Reports for Publication, " we developed and assigned a guideline adherence score (0—17) to each case report. Results: Ninety-six unique journal papers were identified and represented 128 cases. Of the 128 cases, 37% occurred in children under 2 years old, 38% between the ages of 2 and 8 years old, and 23% between the ages of 9 and 18 years old. Twenty-nine percent of cases were the result of an intentional ingestion while 36% were from an unintentional ingestion. Fifty-two percent of cases documented the Latin binomial of the herb ingredients; 41% documented plant part. Thirty-two percent of the cases reported laboratory testing of the herb, 20% documented the manufacturer of the product, and 22% percent included an assessment of the potential concomitant therapies that could have been influential in the adverse events. Mean guideline adherence score was 12.5 (range 6—17). Conclusions: There is considerable need for improvement in reporting adverse events in children following herb use. Without better quality reporting, adverse event reports cannot be interpreted reliably and do not contribute in a meaningful way to guiding recommendations for medicinal herb use.